Biochemical tests in pregnancy - K. Vazhayil, Babitha; S.S, Jayakrishnan (Indian Journal of Pharmacy Practice)
Pregnancy is a normal physiological phenomenon associated with marked hormonal and biochemical changes in the maternal circulation which facilitates the metabolic, vascular and immunological adjustments necessary for the fetus to thrive. Abnormal concentrations of these hormones or of other plasma constituents of fetoplacental origin may indicate gestational pathology. The metabolic changes associated with pregnancy are relatively short lived and thus are rarely harmful to the healthy mother. When pregnancy deviates from its normal course there are many biochemical markers which can be used to assess these abnormalities. As biochemistry is only one part of obstetric care the results should be interpreted in conjunction with clinical and medical imaging data.
Keywords: human chorionic gonadotrophin; alpha fetoprotein